Norwalk-like viruses: demonstration of genomic diversity by polymerase chain reaction. - Green, J (1993)
A reverse transcription-polymerase chain reaction (RT-PCR) amplification procedure was developed for the detection of Norwalk-like viruses in fecal specimens. Ninety-nine fecal specimens collected in the United Kingdom and containing small round-structured virus particles as determined by electron microscopy were tested. They came from 50 outbreaks and 16 sporadic cases of viral gastroenteritis. RT-PCR products of the appropriate size for Norwalk virus RNA were detected in 15 specimens from three outbreaks, suggesting that viruses closely related to Norwalk virus have not been circulating widely in the United Kingdom in recent years. From four isolates, the RT-PCR amplification products of two genomic regions were sequenced and the degree of genomic variation was compared. DNA sequencing of the PCR products revealed strong similarities among strains from the United Kingdom (approximately 97% for both regions amplified) but significant differences from Norwalk virus (67 to 78%). All of the viruses detected by RT-PCR were classified as serotype UK2 by solid-phase immune electron microscopy or enzyme-linked immunosorbent assay. These findings provide evidence of a genomic relationship between Norwalk virus and serotype UK2 small round-structured viruses.